Pengaruh Pemahaman Dan Pendapatan Pedagang Tetap Terhadap Keputusan Menggunakan Asuransi Kebakaran Berdasarkan Padat Penduduk: Studi Kasus Pedagang Sigambal Kec. Rantau Selatan, Kab. Labuhan Batu - Dhea Nita Syafina Rambe; Yenni Samri Juliati Nasution; Budi Dharma (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This research is quantitative descriptive. Data collection techniques were carried out through a list of statements (questionnaire) and documentation studies. The sample in this study was 93 people. Variables are measured using a Likert scale. Hypothesis testing uses multiple linear regression analysis via the t test and f test. Partially, traders' understanding has a positive and significant effect on the decision to use insurance with a value of > (9.187 > 1.661). Traders' income has a positive and significant effect on the decision to use insurance with a value > (2.708 > 1.661). Simultaneous test results show a very real influence on the decision to use insurance for Sigambal traders in Kec. Rantau Selatan District. Labuhan Batu, based on the f test, it is known that Fcount > Ftable (108.348 > 3.10) so that these results identify that the variables Trader Understanding and Trader Income simultaneously influence the Decision to Use Insurance. The determinant coefficient value of 0.707 means that the decision to use insurance for sigambal traders in Kec. Rantau Selatan District. Labuhan Batu can be influenced by traders' understanding and traders' income by 70.7%. The aim of this research is to determine and analyze the influence of Trader Understanding and Trader Income simultaneously on the Decision to Use Insurance.